HUBUNGAN ANTARA RIWAYAT PENGGUNAAN CEFADROXIL DENGAN KEJADIAN STEVEN-JOHNSON SYNDROME DI RSU Dr.SOEDARSO PONTIANAK PERIODE 2007 - 2010 - ., Mega Heksana Devi (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Steven-Johnson syndrome is a hypersensitivity disease was mediated by immune complexes caused by some drugs or infections. The incidence of Stevens-Johnson syndrome induced by drug allergy is increasing in Indonesia. Cefadroxil is a high risk Stevens-Johnson syndrome cause.Objective: To determine association between history of cefadroxil with the occurrence of Steven-Johnson syndrome at RSU dr.Soedarso Pontianak in period 2007- 2010.Method: This is an analytic observational with retrospective study. Ninety five samples were participated. Data was processed by chi square test.Result: Based on the history of the use of cefadroxil, 14 people were diagnosed with Stevens-Johnson Syndrome and 18 people were diagnosed with other forms of Drug Eruption, while based on a history of drug use other types, 26 people were diagnosed with Stevens-Johnson Syndrome and 37 people were diagnosed Drug Eruption. The results show the value of p = 0.817, PR = 1,060, 95% confidence interval = 0.649 to 1.732.Conclusion: There is no significant association between history of consuming cefadroxil and Steven-Johnson syndrome occurrence.Keywords: Steven-Johnson syndrome cefadroxil RSU dr.Soedarso 2007-2010